Integrative and biochemical parameters in rats in the simulation of doxorubicin chronic heart failure and during the use of Β-adrenergic blockers - Belenichev, I. F.; Bak, P. H.; Popazova, O. O.; Ryzhenko, V. P.; Bukhtiyarova, N. V.; Puzyrenko, A.; Бєленічев, Ігор Федорович; Бак, Павло Геннадійович; Попазова, Олена Олександрівна; Риженко, Віктор Павлович; Бухтіярова, Ніна Вікторівна (My University, 2023)
Objective: In the treatment of chronic heart failure, β-blockers are actively used - Carvedilol, Nebivolol, Metoprolol, Bisoprolol, etc. However, they have a number of serious adverse reactions, and their therapeutic efficacy does not always meet the needs of the clinic. All this prompted the creation of a new potential drug Hypertril (bromide 1-(β-phenylethyl)-4-amino-1,2,4-triazolium. We aimed to conduct a comparative assessment of β-blockers of different generations and "Hypertril" in the conditions of modeling the doxorubicin model of chronic heart failure (CHF) in terms of the effect on biochemical markers of myocardial damage and integrative parameters. Material and Method: CHF was modeled on 85 white outbred rats weighing 190–220 g by administering doxorubicin at a total dose of 15 mg/kg, nebivolol (10 mg/kg), carvedilol (50 mg/kg), bisoprolol (10 mg/kg), metoprolol (15 mg/kg) and hypertril (3.5 mg/kg) were administered intragastrically once a day as a suspension 1% starchy mucus for 30 days after 14 days of doxorubicin administration. The cardioprotective effect of drugs was assessed by improving integrative parameters (survival, heart mass index, severity in points) and by normalizing cardiospecific markers (NT-proBNP, D-dimer, eNOS, MB-CPK, and ST2). Result and Discussion: The introduction of Hypertril not only prolonged the life of animals with CHF in comparison with the reference drugs, but also prevented early death and contributed to a decrease in the severity of symptoms (hydrothorax, ascites, scrotal edema). The administration of hypertril to rats with CHF led to a decrease in mortality, a decrease in the heart mass index, in the blood of the main cardiospecific markers to the values of intact animals, and also led to an increase in expression of eNOS, which testified to its significant cardioprotective effect with NO-mimetic effect. The obtained results demonstrated the undoubted advantage of Hypertril over the basic β-adrenergic blockers and experimentally substantiated further in-depth studies to create a drug based on it for the treatment of CHF.
Keywords: Bromide 1-(β-phenylethyl)-4-amino-1,2,4-triazolium; cardioprotection; chronic heart failure; hypertril; endothelial dysfunction; metoprolol; β-blockers